Biceps Squeeze Tenotomy: Technique to Improve Efficiency of Arthroscopic Biceps Tenotomy - Zalneraitis, B. Holt (Arthrosc Tech, 2020)
Biceps tenotomy is a common procedure performed in arthroscopic shoulder surgery. Numerous studies have demonstrated the effectiveness of both biceps tenotomy and tenodesis to relieve pain and restore function for the diagnoses of bicipital tenosynovitis, SLAP tears, rotator interval pulley lesions, and failed SLAP repairs. It is also frequently performed as a concomitant procedure with arthroscopic rotator cuff repair. We report a technique to improve the efficiency of arthroscopic bicep tenotomy using a biceps squeeze maneuver. This is a simple method of manually squeezing the biceps muscle belly while performing the arthroscopic biceps tenotomy. This shortens and tensions the intra-articular portion of the tendon to facilitate a more safe and efficient procedure.